2011
DOI: 10.1109/tnsre.2011.2153874
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Gaze-Sensitive Virtual Social Interactive System for Children With Autism

Abstract: Impairments in social communication skills are thought to be core deficits in children with autism spectrum disorder (ASD). In recent years, several assistive technologies, particularly Virtual Reality (VR), have been investigated to promote social interactions in this population. It is well known that children with ASD demonstrate atypical viewing patterns during social interactions and thus monitoring eye-gaze can be valuable to design intervention strategies. While several studies have used eye-tracking tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 98 publications
(58 citation statements)
references
References 25 publications
0
58
0
Order By: Relevance
“…Eye-contingent games and virtual agents are already used in clinical situations, for example for autism [19,10]. We can envision social gaze interaction being a successful candidate to further develop social therapy or cultural training and learn the consequences of one's gaze behaviour in different situations.…”
Section: Discussionmentioning
confidence: 99%
“…Eye-contingent games and virtual agents are already used in clinical situations, for example for autism [19,10]. We can envision social gaze interaction being a successful candidate to further develop social therapy or cultural training and learn the consequences of one's gaze behaviour in different situations.…”
Section: Discussionmentioning
confidence: 99%
“…For example recent research, albeit using a very small sample, has suggested that virtual reality based systems can be incorporated with eye-tracking, to provide tailored feedback of gaze-sensitive data in relation to the investigation of social interaction impairments in autistic children. This virtual reality system has shown potential as a complement to more real-life social skills training (Lahiri, Warren, and Sarkar, 2011).…”
Section: Future Research and Practical Applicationsmentioning
confidence: 99%
“…For example, eye-based software is already used in clinical settings for autistic patients [6] and this could further deepen the patient's understanding of gaze and its impact. We can also imagine adding a layer of immersion for players in games where the eyes play a crucial role, for example in an immersive Poker tournament in order to bluff or train oneself to not give away clues.…”
Section: Potential For Other Gamesmentioning
confidence: 99%